Entrepreneurial aspirations - Ari Hyytinen; Pekka Ilmakunnas (The Research Institute of the Finnish Economy (ETLA), 2004)
In this paper we study the labour market behavior of employed individuals that have entrepreneurial aspirations in addition to aspirations to switch job, using the Finnish Quality of Work Life Survey from the year 1997. We analyze empirically these two search processes and, inspired by Lazear's (2002) recent jack-of-all-trades hypothesis, focus specifically on the effects of varied experience on them. We report three main findings. First, entrepreneurial aspirations on-the-job are not uncommon. Second, employed people with varied experience are more likely to have entrepreneurial aspirations than others. This finding supports the jack-of-all-trades hypothesis of entrepreneurship. Finally, we propose that the hypothesis is not unique to entrepreneurship, as labour market opportunities available to people with varied experience are likely to be richer than to others. The data support this idea, as the jacks-of-all-trades search on-thejob for a new job more frequently than others. We also briefly consider the policy implications of our findings. – entrepreneurship ; job search ; experience – – Tarkastelemme tässä tutkimuksessa työssäkäyvien halukkuutta etsiä uutta työpaikkaa tai ryhtyä yrittäjäksi käyttäen Työolotiedustelun aineistoa vuodelta 1997. Tutkimme näitä kahta “etsintäprosessia” empiirisesti ja keskitymme Lazearin (2002) “jack-of-all-trades” -hypoteesin (eli ”joka-alan-asiantuntija” -hypoteesin) innoittamana erityisesti siihen, kuinka monipuolinen kokemus vaikuttaa etsintään. Raportoimme kolme päätulosta. (i) Työssäkäyvien halukkuus ryhtyä yrittäjäksi ei ole harvinaista. (ii) Monipuolinen kokemus lisää yrittäjyyshalukkuutta, kuten “jack-of-all-trades” hypoteesi ennustaa. (iii) Väitämme, että monipuolinen kokemus lisää myös uuden työpaikan etsintää, koska se parantaa työmarkkina- asemaa. Empiiriset tuloksemme tukevat myös tätä näkemystä, sillä ne työssäkäyvät, joilla on monipuolista kokemusta, etsivät usein uutta työpaikkaa. Pohdimme lyhyesti myös löydöksiemme politiikkaimplikaatioita. – yrittäjyys ; työn etsintä ; työkokemus
Keywords: J23; J64; L20; 330; Arbeitsplatzsuchmodell; Entrepreneurship-Ansatz; Finnland